Nutrient distribution models and flow patterns in Coastal Waters and Small Islands, Tanjungpinang City, Indonesia - Febrianti Lestari (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2020)
Research has been done on the model of nutrient distribution and current pattern in coastal water of Tanjungpinang City. The research objective was to develop a model of nutrient distribution and current patterns in coastal waters and small islands as an effort to manage the eutofication of coastal waters and small islands in the archipelago. Determining the location of the observations was done by purposive sampling at high tide and low tide at several predetermined research stations. The results showed the nutrient distribution model in the waters of Tanjungpinang Bay, a different distribution pattern compared to the waters of the Dompak Strait, with the distribution of nutrients from the yield model at low tide and at high tide shows the same pattern, which tends to decrease offshore and high in some coastal locations. around the waters of the Sei. Carang estuary which is connected to the waters of Tanjungpinang Bay. The pattern of currents during the highest tide is bandage and full moon in coastal waters and small islands in the area of Tanjungpinang City, which shows that the inlet flows from the west of the waters, then exits towards the north into open water. However, part of the water mass in the presence of small islands around it becomes fragmented causing a turn to the south of the coastal waters of the city of Tanjungpinang, with a maximum current speed of 1.1 m/s.